2018
DOI: 10.3389/fpsyt.2018.00449
|View full text |Cite
|
Sign up to set email alerts
|

Gray Matter Structural Alterations in Social Anxiety Disorder: A Voxel-Based Meta-Analysis

Abstract: The current insight into the neurobiological pathogenesis underlying social anxiety disorder (SAD) is still rather limited. We implemented a meta-analysis to explore the neuroanatomical basis of SAD. We undertook a systematic search of studies comparing gray matter volume (GMV) differences between SAD patients and healthy controls (HC) using a whole-brain voxel-based morphometry (VBM) approach. The anisotropic effect size version of seed-based d mapping (AES-SDM) meta-analysis was conducted to explore the GMV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 100 publications
(122 reference statements)
7
53
0
Order By: Relevance
“…113,133 Social anxiety can be regarded as a position along a continuum ranging from a lack of anxiety, to mild shyness and then social anxiety disorder (SAD), 134,135 so our findings can meaningfully be compared with studies of SAD, which show reduced vmPFC volume. 62,136 The correlation of vmPFC rGMV with lower STE and greater SRE concurs with the well-established role of vmPFC in emotion regulation. A large-scale neuroimaging meta-analysis of affect regulation across 3 distinct domains (fear extinction, placebo effects, cognitive reappraisal) identified vmPFC activation as the only 'common neural regulator' dampening current and anticipated negative affect 66 (see also 137 ).…”
Section: Vbm Findings -Correlations With Social Reward Expectanciessupporting
confidence: 80%
See 1 more Smart Citation
“…113,133 Social anxiety can be regarded as a position along a continuum ranging from a lack of anxiety, to mild shyness and then social anxiety disorder (SAD), 134,135 so our findings can meaningfully be compared with studies of SAD, which show reduced vmPFC volume. 62,136 The correlation of vmPFC rGMV with lower STE and greater SRE concurs with the well-established role of vmPFC in emotion regulation. A large-scale neuroimaging meta-analysis of affect regulation across 3 distinct domains (fear extinction, placebo effects, cognitive reappraisal) identified vmPFC activation as the only 'common neural regulator' dampening current and anticipated negative affect 66 (see also 137 ).…”
Section: Vbm Findings -Correlations With Social Reward Expectanciessupporting
confidence: 80%
“…Recent structural magnetic resonance imaging (sMRI) studies indicate that a number of social traits are reflected in brain macrostructure (regional grey matter volume, rGMV) as assessed by voxel-based morphometry (VBM). 62 Here, we utilized VBM and an unbiased, whole brain analysis, to investigate the possibility of unique and overlapping rGMV correlates of inter-individual differences in social threat and reward expectancies (STE and SRE, respectively) as measured by the LODESTARS.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced vividness of positive future thinking is characteristic of anxious as well as depressed individuals, in addition to anxious expectancies about future social interactions unique to anxiety 72 . Social anxiety can be regarded as a position along a continuum ranging from a lack of anxiety, to mild shyness and then social anxiety disorder (SAD) 15,16,85 , so our findings can meaningfully be compared with studies of SAD, which show reduced vmPFC volume 86,87 .…”
Section: Discussionmentioning
confidence: 89%
“…pSTS rGMV is increased in SAD and shyness (e.g. 87,94 ), and increased pSTS activity to social perceptual cues (eye gaze etc.) has been consistently demonstrated in individuals who are social inhibited, shy, and socially anxious [95][96][97][98] .…”
Section: Discussionmentioning
confidence: 99%
“…The postcentral gyrus also plays an important role in emotional processing, including the identification of emotional significance in a stimulus, generation of emotional states, and regulation of emotion (Kropf et al, 2018). Studies have revealed increased resting-state and task-related activities in the occipital cortex in SAD, which might underlie the enhanced environmental scanning for potentially threatening or feared stimuli in SAD (Wang et al, 2018). Cortical thinning in the postcentral region was functionally related to the severity of social anxiety symptoms in SAD (Syal et al, 2012).…”
Section: Discussionmentioning
confidence: 99%